1995
DOI: 10.1103/physrevc.51.2806
|View full text |Cite
|
Sign up to set email alerts
|

γ decays of proton unbound levels inK37

Abstract: Large discrepancies have been reported between the Gamow-Teller strengths determined from Ca P-delayed proton decay, and the isospin-analog strengths deduced from "Cl(p, n) studies. Some of these discrepancies could be removed if the Ca daughter level at 3.24 MeV in K had I'~forty times bigger than its I'", and not negligibly small as assumed in the initial analysis of the Ca P decay. We studied proton and p-ray branching ratios of low-lying K levels populated via the Ca(p, o) reaction. We find that the 3.24 M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…The excitation energies of 37 Ar were determined by the use of the well-known excitation energies of 13 N, 16 F, 18 F, 24 Al, 26 Al, 35 Ar, and 37 Ar. They were measured under the same conditions as the targets of MgO, 40 Ca 35 Cl 2 + PVA, and 40 Ca 37 Cl 2 + PVA.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The excitation energies of 37 Ar were determined by the use of the well-known excitation energies of 13 N, 16 F, 18 F, 24 Al, 26 Al, 35 Ar, and 37 Ar. They were measured under the same conditions as the targets of MgO, 40 Ca 35 Cl 2 + PVA, and 40 Ca 37 Cl 2 + PVA.…”
Section: Methodsmentioning
confidence: 99%
“…Subsequently, the assumption in the analysis that all proton-unbound daughter states in 37 K decayed by proton emission was questioned. The studies of 36 Ca(p, γ ) 37 K [17] and 40 Ca(p, α) 40 K [18] reactions suggested that a few protonunbound states in 37 K above the proton separation energy had significant probabilities of undergoing γ decay. Actually recalculation of the B(GT) distribution by taking both the delayed proton emission and the γ decay into account reduced a large part of the difference [19,20].…”
mentioning
confidence: 99%
“…Therefore, only 𝑝-𝛾 coincidence of the 36,37 Ca decays can be analyzed. According to the high-resolution study, [32,41] a 𝛾 line at 1184 keV was identified as the de-excitation after the proton decay (𝐸 p =∼1.4 MeV) of IAS in 36 K to the first excited state of 35 Ar (𝐸 𝑥 = 1184 keV). A similar situation was also found in the de-excitation after the decays of excited states of 37 K to the first excited state of 36 Ar (𝐸 x = 1970 keV) according to Ref.…”
Section: Literaturementioning
confidence: 99%
“…[25−27] Significant progress has been made on both experimental and theoretical sides. [28−37] The study of the 𝛽 decay of 36 Ca can also give information about the properties of near-threshold states in 36 K that could be important resonances in the 35 Ar(p,𝛾) 36 K reaction of astrophysical interest. [32,38−41] In traditional experiments, the isotopes of interest were usually im-planted into a silicon detector, where their decay could be measured.…”
mentioning
confidence: 99%
“…The final results are summarized in Table I. We nance are derived from the adopted resonance strength and the recently measured branching ratio Γ γ /Γ p = 0.545 ± 0.030 (weighted average from [16,7,17]). The total width Γ = 348 ± 28 meV corresponds to a lifetime of τ = 1.89 ± 0.15 fs which is in agreement with the upper limit τ < 3 fs [5] and in rough agreement with τ = 0.7 ± 0.5 fs [6].…”
mentioning
confidence: 99%